Dust remobilization in fusion plasmas under steady state conditions. (11th January 2016) - Tolias, P; Ratynskaia, S; De Angeli, M; De Temmerman, G; Ripamonti, D; Riva, G; Bykov, I; Shalpegin, A; Vignitchouk, L; Brochard, F; Bystrov, K; Bardin, S; et al.
Abstract: The first combined experimental and theoretical studies of dust remobilization by plasma forces are reported. The main theoretical aspects of remobilization in fusion devices under steady state conditions are analyzed. In particular, the dominant role of adhesive forces is highlighted and generic remobilization conditions—direct lift-up, sliding, rolling—are formulated. A novel experimental technique is proposed, based on controlled adhesion of dust grains on tungsten samples combined with detailed mapping of the dust deposition profile prior and post plasma exposure. Proof-of-principle experiments in the TEXTOR tokamak and the EXTRAP-T2R reversed-field pinch are presented. The versatile environment of the linear device Pilot-PSI allowed for experiments with different magnetic field topologies and varying plasma conditions that were complemented with camera observations.